Cough management in primary, secondary and tertiary settings. (December 2017) - Wang, Kay; Milojevic, Nikki; Sheinman, Bryan; Usmani, Omar S.
Abstract: This review reflects upon the management of cough in primary, secondary and tertiary care settings. It reviews the burden of cough, the diagnostic tools employed to investigate the cause of cough and pragmatic treatment strategies. A clinical case vignette presenting in primary care highlights the challenges of managing cough by family practitioners. An approach to establishing a persistent cough clinic service in secondary care is described. Finally, the entity of idiopathic cough in tertiary care and the specialist approaches to treating recalcitrant cough are addressed.